2022
DOI: 10.1039/d2ay01014c
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase–Cu3(PO4)2 hybrid nanoflowers for electrochemical detection of dichlorvos using square-wave voltammetry

Abstract: Immobilization of enzymes is one of the key steps in the development of high-performance enzymatic electrochemical biosensors, and various nanostructured materials have been designed and developed to achieve this goal....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…AChE hNFs/Au NPs/GO/glassy carbon electrode showed favorable detection performance due to the AChE hNFs have large surface area and provide the affinity to substrates with improved catalytic activity (Figure 2B). This biosensor enabled the determination of dichlorvos with a detection limit of 0.07 pM and exhibited great detection accuracy and recoveries about 98.65%–103.43% in real agricultural samples 56 . In another study, the same researchers reported the fabrication of in situ growth of aptamer (Apt) based AChE hNFs.…”
Section: Application Of Hnfsmentioning
confidence: 97%
See 2 more Smart Citations
“…AChE hNFs/Au NPs/GO/glassy carbon electrode showed favorable detection performance due to the AChE hNFs have large surface area and provide the affinity to substrates with improved catalytic activity (Figure 2B). This biosensor enabled the determination of dichlorvos with a detection limit of 0.07 pM and exhibited great detection accuracy and recoveries about 98.65%–103.43% in real agricultural samples 56 . In another study, the same researchers reported the fabrication of in situ growth of aptamer (Apt) based AChE hNFs.…”
Section: Application Of Hnfsmentioning
confidence: 97%
“…This biosensor enabled the determination of dichlorvos with a detection limit of 0.07 pM and exhibited great detection accuracy and recoveries about 98.65%-103.43% in real agricultural samples. 56 In another study, the same researchers reported the fabrication of in situ growth of aptamer (Apt) based AChE hNFs. They utilized the aptamer of AChE for the in situ growth of AptAChE hNFs on the carbon paper.…”
Section: Electrochemical Detection Based On Hnfsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most organophosphorus do not have inherent redox activity. In order to detect organophosphorus without inherent redox activity, electrochemical sensors use the inhibition of organophosphorus on enzyme activity to detect organophosphorus pesticides [11][12][13]. However, complex detection conditions, including the temperature, pH value, and solvent type, will affect the detection activity of the enzymes.…”
Section: Introductionmentioning
confidence: 99%